Hubungan Dukungan Suami Dengan Minat Ibu Dalam Pemilihan Metode Kontrasepsi Jangka Panjang Pada Ibu Multiparitas Di Puskesmas Ciparay DTP Kab. Bandung Tahun 2024 - Rahayu, Indah; Liska, Cici; Destiani S, Tria (Jurnal Syntax Fusion, 2024)
In Indonesia, the number of active family planning participants is 63.7% of family planning acceptors choosing injections as a contraceptive, 17% choosing pills, 7.4% choosing implants, 7.4% choosing intrauterine devices (IUD) and 4.4% others. In general, people choose non-MKJP methods, so MKJP family planning methods such as Intra Uterine Devices (IUD), Implants, Male Operative Medical (MOP) and Female Operative Medical (MOW) are less popular (BKKBN, 2019). The cause of low MKJP is influenced by husband's support. Husband's support has a big influence on the decision to use or not and what method to use. The form of support given to couples can be in the form of reminding them to take control, taking them to get family planning services, providing funds and giving approval for the contraceptives used by their partners. The more mothers who receive approval and support from their husbands to use MKJP, it is hoped that more potential acceptors will use MKJP (Syahdrajat, 2015). The design of this research is Correlation Analysis. This research was carried out using a cross sectional design to analyze variable data collected at a certain point in time. The results of the research regarding the relationship between husband's support and the interest of multiparous mothers in choosing a long-term contraceptive method are the results of the Chi Square test showing a P value of 0.004 with a significance level of α 5% (0.05). Based on these results, the P value is 0.004 <α (0.05), this means that it is significant or there is a relationship between husband's support and the mother's interest in choosing a long-term contraceptive method for multiparous mothers.